2017
DOI: 10.1007/978-981-10-5948-3
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Reduction, the Private Sector, and Tourism in Mainland Southeast Asia

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Firms compete for employees as well as customers. It is likely the existence of additional jobs opportunities created by foreign firms result in increased competition for employees, thus pressuring local firms to increase benefits to attract workers (Hipsher, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firms compete for employees as well as customers. It is likely the existence of additional jobs opportunities created by foreign firms result in increased competition for employees, thus pressuring local firms to increase benefits to attract workers (Hipsher, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has been pointed out a job which looks like exploitation and offers what is considered poor working conditions from the viewpoint of the activist or visitor from a developed economy might look very appealing to individuals living in poverty with few other options. These "sweatshop" jobs can be perceived as the first rung out of extreme poverty to a person living in a developing or least developed economy (e.g., Hipsher, 2017;Powell, 2014;Sachs, 2005, p. 11). The opinion has also been expressed the removal of livelihood options by limiting the activities of MNEs in developing economies is likely to harm people in most need of livelihood opportunities and the international community should respect the right of individuals in developing and less developed economies to make their own livelihood and purchasing choices (e.g., Flew, 1989;Levin, 1999;Prahalad, 2005).…”
Section: Wealth Creation Approachmentioning
confidence: 99%
“…Namun demikian, strategi tersebut banyak dikritik sebagai alat kapitalisme global yang cenderung mengeksploitasi masyarakat miskin demi keuntungan industri pariwisata dan kebutuhan wisatawan asing semata (Hipsher, 2017). Hal ini membawa situasi dilematik.…”
Section: Tinjauan Pustakaunclassified
“…A number of studies by contrast have concluded that the role of growth in the non-agricultural sector in poverty reduction is increasing Christiaensen et al (2011) and Himashu et al (2013). Warr (2001) used econometric analysis on pooled data of Indonesia., Thailand, Malaysia and the Philippines, the author found these countries experience the greatest poverty reduction due to tertiary sector. Likely Warr and Wang (1999) used time-series analysis for Taiwan, the finding of this model shows that industrial growth is most poverty reducing factor.…”
Section: Literature Reviewmentioning
confidence: 99%